Minum Khamer Dalam Perspektif Hukum Pidana Islam - Ghina Aulia Rizky; Mita Mita; Radiatul Hafifah; Surya Sukti (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Khamar is a drink that has the potential to be intoxicating if consumed at normal levels by a normal person, it is unlawful to drink it. Consuming wine contains a major sin, although there are benefits in human life, but the harm is greater than the benefits. Khamar is regulated in Islamic criminal law because consuming it is an offence. The aim of this research is to analyze the punishment for perpetrators of the crime of khamar in Islamic criminal law. Jarimah drinking alcoholic beverages (khamr) is a case of jarimah hudud, and is threatened with a had punishment, namely the punishment of not less than 40 lashes and may be more. According to the agreement of the ulama, the punishment for those who drink khamr was initially 40 (forty) lashes. Meanwhile, the friends agreed to stipulate 80 (eighty) lashes for reasons of benefit. With the existence of the law of law, more and more people will experience the deterrent effect of drinking alcohol.